Ambidextrous leadership as a catalyst for employee innovation: Its impact on the competitive advantage - Muzakki, Muzakki; Herryanto, Asep; Permadi, Edo Galih (Sekolah TInggi Ilmu Administrasi dan Manajemen Kepelabuhan (STIAMAK) Barunawati Surabaya, 2024)
The aim of this study is to explore the relationship between ambidextrous leadership and employee innovation, as well as its impact on competitive advantage. The respondents participating in this research included 147 individuals comprising employees and branch leaders of the Small and Medium Enterprises Bank of East Java. The collected data were analyzed using SEM PLS version 3.0. The findings of this study indicate that ambidextrous leadership has a significant effect on employee innovation and competitive advantage. Furthermore, employee innovation also exerts a significant influence on competitive advantage. This research enriches the literature on ambidextrous leadership by emphasizing the importance of this leadership style in fostering employee innovation and enhancing competitive advantage. It reinforces the assumption that leaders who can balance exploration and exploitation are likely to achieve better outcomes.